TECHNOLOGIES FOR TEACHING ENGLISH THROUGH MULTIMEDIA APPLICATIONS - Makhmudova Shakhnozaxon Odiljon kizi (Modern American Journals, 2025)
The advancement of digital technologies has had a profound impact on education, particularly in the teaching and learning of foreign languages. Among the most influential innovations are multimedia applications, which offer dynamic and interactive learning experiences. In English as a Foreign Language (EFL) classroom, multimedia tools provide diverse opportunities for enhancing linguistic competence. They allow learners to engage with authentic materials, including videos, audio, animations, and interactive exercises. This creates a more immersive and stimulating environment compared to traditional textbook-based instruction.Multimedia technologies address various learning styles—visual, auditory, and kinesthetic—by combining images, sound, and motion. Students are more likely to stay motivated and engaged when learning is supported by such tools. Interactive programs can simulate real-life conversations and scenarios, providing learners with practical communication experience. Listening skills improve through exposure to different accents and contexts via multimedia content. Reading and writing skills can also be developed through digital storytelling platforms and language apps.Research shows that students using multimedia in language learning environments outperform those who rely solely on traditional methods. Teachers report that students demonstrate higher retention rates, better pronunciation, and improved comprehension. The integration of multimedia into the curriculum supports constructivist learning approaches, where students actively construct knowledge rather than passively receive it. This shift encourages independent learning and critical thinking.
Keywords: Multimedia applications, English as a Foreign Language (EFL), language learning technologies, digital tools in education, interactive learning